Phân tích trượt sườn dốc theo phương pháp mô hình vật lý có xét đến điều kiện tương thích của lực tương tác - An, Phan Tiến; Phiệt, Phan Trường; Hoàng, Nguyễn Văn; Hùng, Vũ Đình (Vietnam Journal of Earth Sciences, 2012)
summaryAnalysis of slope limit equilibrium slip cycle by physical method regarding to compatible interslice force conditionExisting traditional slope stability analytical methods use some assumptions such as neglection of interslice forces, resulted interslice force line-focus, and slope angle of acting force. Thecommon point of all the existing slope stability analysis methods is that the compatibility of the sliding and resisting forces on the two parts of the slide masses divided a slice are not taken into account.This paper presents the summary of the mathematical formulation of the "compatible" method to determine the equilibrium slip cycle, considering the compatible interslice force condition, and presentsactual programming analysis for several slope conditions for discussion. The application of the slope analysis by this "compatible" method shows comparable results with the results obtained byBishop simplified method.